JAK2V617F Mutation Promoted IL-6 Production and Glycolysis via Mediating PKM1 Stabilization in Macrophages - Li, Rongqing; Sun, Na; Chen, Xin; Li, Xueqin; Zhao, Jie; Cheng, Wanpeng; Hua, Hui; Fukatsu, Masahiko; Mori, Hirotaka; Takahashi, Hiroshi; Ohkawara, Hiroshi; Fukami, Miwa; et al. (Frontiers in Immunology, 2021)
A substitution mutation of valine to phenylalanine at codon encoding position 617 of the Janus kinase 2 (JAK2) gene (JAK2V617F) has been detected in myeloid cells of some individuals with higher levels of proinflammatory cytokine production such as interleukin (IL) -6. However, the mechanisms by which JAK2V617F mutation mediating those cytokines remain unclear. We, therefore, established JAK2V617F-expressing murine macrophages (JAK2V617F macrophages) and found that the levels of p-STAT3 were markedly elevated in JAK2V617F macrophages in association with an increase in IL-6 production. However, inhibition of STAT3 by C188-9 significantly decreased the production of IL-6. Furthermore, the JAK2V617F mutation endowed macrophages with an elevated glycolytic phenotype in parallel with aberrant expression of PKM1. Interestingly, silencing of PKM1 inactivated STAT3 in parallel with reduced IL-6 production. In contrast, ectopic expression of PKM1 elevated IL-6 production via STAT3 activation. Importantly, the JAK2V617F mutation contributed to PKM1 protein stabilization via blockade of lysosomal-dependent degradation via chaperone-mediated autophagy (CMA), indicating that the JAK2V617F mutation could protect PKM1 from CMA-mediated degradation, leading to activation of STAT3 and promoting IL-6 production.